Snow cover at the Akademik Vernadsky station: response on wind, temperature and precipitation variations - Vitalii Shpyg; Oleksandr Shchehlov; Denys Pishniak (Ukrainian Antarctic Journal, 2024)
We analyze the changes in snow depth at different time scales (from within a day to over many years) and its dependence on the precipitation phases, wind regime, and air temperature. The study employs observational data for snow cover and regular meteorological records of the air temperature (2 m), precipitation, and wind (direction and speed at 10 m) in 2002–2022. The data were processed by classical climatological methods. To compare the data on snow depth with precipitation phases, air temperature, wind speed and direction, we used temporal interpolation. It is shown that solid precipitation occurs most often, when the annual distribution of precipitation is considered. A significant percentage of precipitation in the liquid phase is observed during the Antarctic summer and Antarctic autumn. The portion of the mixed precipitation is the smallest throughout the year. The influence of the precipitation phases on the accumulation/melting of snow has seasonal character. The period from April to November is favorable for snow accumulation. In December, the solid precipitation leads to an increase in snow depth, but the mixed and liquid phases are accompanied the melting of the snow cover. The most significant snow cover grows smaller in January-February due to melting. The emphasis is on the local effect of the snow depth decrease due to strong winds in a setting with the accompanying effect of the thermal factor. Further analysis showed that the parameter most closely associated with snow cover depth reduction was a combination of wind speed and direction. Snow cover depth was reduced the most in January–March due to melting, yet on a daily scale, the reduction’s intensity was not the highest. The highest frequency of cases of intense reduction in snow cover depth by more than 1 cm/3h is seen if the wind is either northerly, northeasterly, or southerly. The most frequent reduction in snow cover depth is seen under the northerly and northeasterly winds and positive temperatures. The north and northeastern air masses’ advection is mostly associated with heat advection, and thus, the snow cover depth is reduced by melting. The eastern, northeastern, and southeasterly winds can be connected to the effect of the foehn winds due to the closeness of the continent. The most frequent occurrence of a significant reduction in the snow cover under the southern wind is noted under a high wind speed and negative air temperature.